The Effect of Self-Efficacy and Self-Concept on Increasing Optimism in Achieving Targets in Employees of Bank Syariah Indonesia (BSI) Case Study of BSI KCP Medan Aksara - Fauziah Amarani; Sugianto; Muhammad Lathief Ilhamy Nasution (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aims to analyze the influence of self-efficacy on increasing optimism in achieving targets for BSI KCP Medan Aksara employees. Quantitative research method using the SPSS application. The data collection technique was carried out by distributing questionnaires to the relevant research samples. The population in this study were all employees at PT. Bank Syariah Indonesia KCP Medan Aksara with a sample size of 30 employees. The results of testing the coefficient of multiple determination between self-efficacy (X1) and self-concept (X2) obtained an R value of 0.558, so it can be said to be strongly correlated. From the calculation, the coefficient of determination or Adjusted R Square is 0.260 or 26%. This shows that the self-efficacy and self-concept variables have an influence on the optimism variable by 26%, while the remaining 74% is influenced by other factors not explained in the research.